Commodities consensus: Neoextractivism and enclosure of the commons in Latin America - Svampa, Maristella Noemi (2015)
In this paper, we propose an approach to the debates about development and the intensification of the extractive model at four different levels.-First, I will present two general concepts that are the framework for my proposal:Commodities Consensus and Extractivism- Secondly, I will describe a recursive, dynamic approach to the differentphases of the Commodities Consensus- In the third place, I want to talk about the socio-environmental conflicts in Latin America-Finally, Iwill discuss the progressive shift towards new forms of dependency, especially in relation with China.